2018
DOI: 10.31397/seeij.v2i1.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Firm’s Characteristic and Corporate Governance to Sustainability Report Disclosure

Abstract: The purpose of this study was to analyze the effect of company’s characteristic which are profitability (ROA), leverage (DER), liquidity (CR), company size (SIZE), and corporate governance proxied by board of directors and audit committee (KA) to disclosure of sustainability reports (SR). The study had 105 samples of manufacturing companies listed in Indonesia Stock Exchange and 262 manufacturing companies listed on Malaysia Exchange in year 2013-2015. Data analysis using regression logistic method with E-view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
4
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 3 publications
8
31
4
9
Order By: Relevance
“…Prior studies by Lucia and Panggabean; Fitri and Yuliandari; Khafid and Mulyaningsih found that profitability has a positive effect to the sustainability reporting [11][12][13].…”
Section: A Financial Performance and Sustainability Reportingmentioning
confidence: 99%
“…Prior studies by Lucia and Panggabean; Fitri and Yuliandari; Khafid and Mulyaningsih found that profitability has a positive effect to the sustainability reporting [11][12][13].…”
Section: A Financial Performance and Sustainability Reportingmentioning
confidence: 99%
“…Sustainability reporting is able to help a company to evaluate company performance results effectively. This makes companies increasingly have more value in the business world, improve financial performance, and build company legitimacy (Lucia & Panggabean, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The result of the study shows that at the ASEAN level, Indonesia is in the lowest position in conducting sustainability report disclosure. Lucia & Panggabean (2018) in their research in manufacturing companies listed on the IDX and Malaysia Exchange in 2013-2015, resulting in the value of sustainability report disclosures of 0.041 in Indonesia and 0.036 in Malaysia. This finding states that in Indonesia it is still relatively low in disclosing sustainability reports.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations